The role of organisational antecedents in driving entrepreneurial orientation and firm performance - Verachia, Abdullah (My University, 2017)
The aim of this study was to analyse and investigate the link between organisational antecedents that enhance corporate entrepreneurship, and entrepreneurial orientation, followed by entrepreneurial orientation’s impact on firm growth and performance. The study focused primarily on recent graduates in companies operating in South Africa. The organisational antecedents analysed were management support, work discretion, rewards and reinforcement, time availability, and organisational boundaries. The entrepreneurial orientation factors used were proactiveness, risk-taking, and innovativeness. The impact of entrepreneurial orientation was measured against firms’ growth and performance. A sample of 193 recent graduates, employed in an array of sectors in South Africa was analysed. The findings reveal that recent graduates place a particular emphasis on management support, and rewards and reinforcement as particular enablers for creating the context for corporate entrepreneurship. A significant positive relationship between these antecedents and entrepreneurial orientation, and a strong association between entrepreneurial orientation and firm growth and performance was found. Population trends reflect that 58.13 percent of South Africans are under the age of 29 (Stats SA, 2016), reflecting that young people, under the age of 30, will serve as the dominant demographic in the workforce in South Africa, over the next 15 years. This study was thus particularly relevant as it aligns the changing external environment that compels companies to become more entrepreneurial, with the perspective of a new generation of workforce that will be primarily responsible for driving this change.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation Johannesburg, 2017
Keywords: Entrepreneurship--South Africa; Business enterprises--South Africa; Organizational effectiveness--South Africa